Advance in the knowledge and actual conservation status of Tumbes Crocodile (Crocodylus acutus Cuvier, 1807) - Escobedo Galván, Armando H. (2004)
The conservation status in Peru of the Tumbes Crocodile is described. This country is the southern limit of crocodile distribution and for that is catalogued as rare at this zone. This has been generating ex situ management programs to encourage its conservation. However, crocodile population have diminished and become endangered as consequence of deforestation, climatic change, the anthropogenic activities and the unknown uses it can provide.